ON THE READY OF A FOREIGN LANGUAGE TEACHER TO WORK IN PRIMARY SCHOOL - Shtelmakh, H.B. (Pedagogy of Higher and Secondary Education, 2010)
The article deals with different ways of training of foreign languages teachers for the work in primary school.